Traditional knowledge of Mun Condo cultivation: Comparison of cassava cultivation using natural and chemical fertilizers - ทรัพย์สวนแตง, สมเกียรติ; จันทจร, ทรงคุณ; โกเศยะโยธิน, มาริสา (Ratchaphruek Journal, 2018)
This research was conducted in Uthong and Don Chedi Districts, Suphanburi Province. Research results indicate that community centers for plant pest control in each district play a role as transmission centers for Mun Condo planting techniques in order to encourage farmers to increase their yields. Those techniques have become widely spread among farmers in Suphanburi and other provinces in the region. Cassava cultivation using natural fertilizer gave greater yield than using chemical fertilizer. Trade barriers in some countries is the main problem with the export of Thai cassava. The main problem of cassava exporting is the trade barriers in some countries.